Kelayakan Abu Terbang PLTU Buntoi Sebagai Campuran Beton Geopolimer - Dadang Suriyana; Liliana Sahay; Okta Meilawaty (​Institute for Researches and Community Services Universitas Muhammadiyah Palangkaraya, 2021)
The main basic ingredients needed for the manufacture of this geopolymer material are materials that contain a lot of silica and aluminia elements. The 1st stage test was carried out to determine the geopolymer paste with the maximum compressive strength at the ratio of NaOH to Na2SiO3 of 1; 1.5; 2; 2.5. The second stage of testing was carried out using a geopolymer paste with the highest compressive strength, namely the ratio of NaOH to Na2SiO3 of 2.5 with a compressive strength of 22.56 MPa. Based on the results of the compressive strength test, the maximum compressive strength at the age of 28 days is 7.64 MPa. The results of the compressive strength of concrete are much lower than the compressive strength of the paste, it shows that the paste does not bind too much with the aggregate. This is evidenced by the results of the compressive strength of conventional concrete which is much higher than that of geopolymer concrete using the same aggregate. With the results of the maximum compressive strength at the age of 28 days is 29.51 MPa.